2020
DOI: 10.1158/1055-9965.epi-20-0331
|View full text |Cite
|
Sign up to set email alerts
|

Autoantibodies in Early Detection of Breast Cancer

Abstract: In spite of the progress made in treatment and early diagnosis, breast cancer remains a major public health issue worldwide. Although modern image-based screening modalities have significantly improved early diagnosis, around 15% to 20% of breast cancers still go undetected. In underdeveloped countries, lack of resources and cost concerns prevent implementing mammography for routine screening. Noninvasive, low-cost, blood-based markers for early breast cancer diagnosis would be an invaluable alternative that w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 114 publications
(168 reference statements)
0
16
0
Order By: Relevance
“…The immune system responds to these non-self antigens, producing specific autoantibodies. Tumor-associated (TA) autoantibodies have been observed in patients with various tumors, including breast [ 4 ], prostate [ 5 , 6 ], lung [ 7 ], colorectal [ 8 ], ovarian [ 9 , 10 ], and liver [ 11 ], and have become of interest as cancer biomarkers because they can be easily detected in serum via minimally invasive blood collection [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…The immune system responds to these non-self antigens, producing specific autoantibodies. Tumor-associated (TA) autoantibodies have been observed in patients with various tumors, including breast [ 4 ], prostate [ 5 , 6 ], lung [ 7 ], colorectal [ 8 ], ovarian [ 9 , 10 ], and liver [ 11 ], and have become of interest as cancer biomarkers because they can be easily detected in serum via minimally invasive blood collection [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Tumor-associated autoantibodies have become one of the most important areas in biomarker exploitation for early cancer detection, as autoantibody detection could precede the clinical symptoms of breast cancer 7 , 13 , 19 . Increasing studies have shown valuable role of autoantibodies in the diagnosis, prognosis and prediction of treatment effect of many types of cancers 20 , 21 .…”
Section: Discussionmentioning
confidence: 99%
“…For breast cancer, numerous serum autoantibodies have been reported with potential early diagnostic value, whereas only few have been investigated in detail to evaluate the diagnostic utility. To date, individual autoantibodies are shown to have low clinical sensitivity, thus cannot be applied to screen early breast cancer 7 . To resolve the issue of low sensitivity for early diagnosis, increasing studies have developed autoantibody panels 32 - 34 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies have demonstrated that autoantibodies against tumor-associated antigens (TAA), so called TAAb, could be used for BC detection. 8,9 As potential tumor biomarkers, TAAb have several advantages:…”
Section: Introductionmentioning
confidence: 99%